Enhancing Teacher Commitment to Improve Educational Quality: A Literature Reviews - Variani, Herlin; Hadiyanto, Hadiyanto; Sulastri, Sulastri (International Journal of Educational Dynamics, 2024)
This study aims to examine the factors influencing teacher commitment and its impact on improving the quality of education in Indonesia. Teacher commitment is essential for aligning personal and institutional goals, fostering efficiency in task completion, and addressing challenges in 21st-century education. A literature reviews method was employed, analyzing study from various journals to gather and summarize relevant findings. The review focused on strategies to enhance teachers' dedication, including professional development, supervision, and recognition of achievements. The results reveal that high teacher commitment reduces issues like tardiness, absenteeism, and poor performance. Effective strategies include rewarding responsible educators, enforcing discipline, providing learning resources, and fostering teamwork. Additionally, organizational factors such as clear vision, mission, and values-based recruitment contribute to cultivating teacher responsibility. The findings emphasize the role of school administrators in promoting teacher engagement through mentorship, training, and collaboration. The study concludes that committed educators positively impact student achievement and institutional growth. Schools must prioritize strategies to support teachers' personal and professional development to ensure high educational standards.